The myth of zero-sum responsibility: towards scaffolded responsibility for health - Levy, N; Savulescu, J (Brill Academic Publishers, 2023)
Some people argue that the distribution of medical resources should be sensitive to agents’ responsibility for their ill-health. In contrast, others point to the social determinants of health to argue that the collective agents that control the conditions in which agents act should bear responsibility. To a large degree, this is a debate in which those who hold individuals responsible currently have the upper hand: warranted appeals to individual responsibility effectively block allocation of any significant degree of responsibility to collective agents. We suggest that a different understanding of individual responsibility might lead to a fairer allocation of blame. Scaffolded agency is individual agency exercised in a context in which opportunities and affordances are structured by others. Appeals to scaffolded agency at once recognize the role of the individual and of the collective agents who have put the scaffolds in place.